A review of issues and challenges of implementation of patient blood management - Azita Chegini; Ali Jamalian; Mohammad Reza Abolhassani; Ali Boroujerdi Alavi (Asian Journal of Transfusion Science)
INTRODUCTION: Patient blood management (PBM) is outlined as evidence-based medical and surgical concepts with a multidisciplinary method. AIMS AND OBJECTIVES: The aim of this article is to review the PBM implementation and analyses the issues, challenges, and opportunities. METHODOLOGY: In this article, we have an overview of PBM implementation in literature and our experience in one hospital in Iran. We used databases including Embase, CINAHL, Scopus, Google Scholar, Google, Science Direct, ProQuest, ISI Web of Knowledge, and PubMed to attain the related literature published in the English language. RESULTS: There are different barriers and challenges of implementation of PBM, such as hospital culture confrontation, reduced staff with restricted time, lack of interdisciplinary conversation, change of practice, the lack of experience with PBM, the feasibility to integrate PBM, electronic documentation and schedule budget for required instruments, resources, and personnel. Hospitals differ globally in the aspect of infrastructure, personnel and properties, and it is necessary to individualize according to the local situation. CONCLUSION: The review highlights the importance of PBM and its implementation for obtaining patient safety. PBM establishing in hospitals as a complex process have different challenges and barriers. Sharing experiences is essential to success in the PBM programs. Cooperation between countries will be useful in PBM spreading.